2013
DOI: 10.1080/09593330.2013.861022
|View full text |Cite
|
Sign up to set email alerts
|

Methylene blue biosorption by pericarp of corn, alfalfa, and agave bagasse wastes

Abstract: The presence of dyes in effluent is a matter of concern due to their toxicologic and aesthetical effects. In this research, locally available agro-industrial wastes (Zea mays pericarp, ZMP; Agave tequilana bagasse, ATB; and Medicago sativa waste, MSW) were used as alternative low-cost adsorbents for the removal of methylene blue (MB) from aqueous solutions. The adsorbents were characterized physically and chemically by Fourier transform infrared, scanning electron microscopy, potentiometric titrations, and N2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…In particular, the increasing costs of conventional adsorbents certainly make lignocellulosic-based materials, composed by natural polymers, one of the most attractive bioadsorbents for wastewater treatment (Sharma and Rajesh, 2014;Kumar et al, 2014). Different studies have demonstrated that lignocellulosic-based polymers have exceptional removal capabilities for certain pollutants such as dyes and metal ions as compared to other low-cost adsorbents and commercial activated carbons (Batzias et al, 2009;Rosas-Castor et al, 2014;Sidiras et al, 2013;Velazquez-Jimenez et al, 2013). Thus, cellulose-based biocomposites, has been widely used in wastewater purification due to its good biocompatibility, and excellent handling, which can be easily formulated into spheres, membranes and hollow fibres.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the increasing costs of conventional adsorbents certainly make lignocellulosic-based materials, composed by natural polymers, one of the most attractive bioadsorbents for wastewater treatment (Sharma and Rajesh, 2014;Kumar et al, 2014). Different studies have demonstrated that lignocellulosic-based polymers have exceptional removal capabilities for certain pollutants such as dyes and metal ions as compared to other low-cost adsorbents and commercial activated carbons (Batzias et al, 2009;Rosas-Castor et al, 2014;Sidiras et al, 2013;Velazquez-Jimenez et al, 2013). Thus, cellulose-based biocomposites, has been widely used in wastewater purification due to its good biocompatibility, and excellent handling, which can be easily formulated into spheres, membranes and hollow fibres.…”
Section: Introductionmentioning
confidence: 99%
“…Although the adsorption capacity of these hydrophobic clays is lower than the unmodified clay, the removal of MB is still significant and even higher than other recently studied adsorbents like corn cob (111 mg/g), and agave bagasse waste (156 mg/g) [20]. Castile nutshells (141 mg/g) [1], grape stalks, and corn barks with 106 and 31 mg/g, respectively have also been studied for the elimination of MB and display a lower adsorption [21].…”
Section: Adsorption Testsmentioning
confidence: 99%
“…Some techniques that are efficient but expensive have been reported, such as the use of activated charcoal [25], which has been implemented in small industries [26]. Nevertheless, these techniques also present several disadvantages, such as high reagent, high energy consumption, and low kinetics [27].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of textile wastewater containing indigo dye is one of the most difficult because the dye is of synthetic origin and has a molecular structure aromatic complex, which is more stable and harder to biodegrade [27][28][29]. The alteration of their chemical structures can result in the formation of new compounds xenobiotics, which may be more toxic than the potential compounds [30].…”
Section: Introductionmentioning
confidence: 99%